Analysing the Views of School of Foreign Languages Instructors about Organizational Culture - Devrim AKMAN; Didem KOŞAR (Anı Publishing, 2021)
This study aims to investigate the views of school of foreign languages instructors about organizational culture. The study is designed in qualitative research method and as a case study. The study was conducted with 15 school of foreign languages instructors who were selected by maximum variation sampling method during the 2018 and 2019 academic year in Ankara. Semi structured interviews were conducted to gather data and content analysis was used to analyse the data. The study emphasises that for the powerful school culture, instructors should focus on orientation, social activities, merit, and democratic management style.